The making of the middle class : toward a transnational history of the middle class - López, A. Ricardo, 1974-; Weinstein, Barbara (Radical perspectives., 2012)
The contributors question the current academic understanding of what is known as the global middle class. They see middle-class formation as transnational and they examine this group through the lenses of economics, gender, race, and religion from the mid-nineteenth century to today.